STUDY ON DETERMINANTS OF SUCCESSFUL OUTCOME IN ICSI PREGNANCIES IN A TERTIARY CARE CENTRE - Vijayan, Devika; Nalligounder, Prema; mohan, Reji; Balakrishnan, Sheila (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: A descriptive study was done at the government medical college in Thiruvananthapuram to find out the determinants of the successful outcome of intracytoplasmic sperm injection (ICSI) pregnancies. Methods: The study was done on 60 ART-conceived patients who underwent ICSI and became positive for pregnancy during 1 year. Their pregnancy was followed up, and data was collected in a structured proforma about determinants of successful outcomes. Results: Out of 60 in vitro fertilization (IVF)-conceived subjects (n=60), the maximum age group (40%) that underwent IVF treatment was between 31 and 35 years old, and they belonged to an upper-lower socio-economic status. 45% of patients had a normal body mass index, 46.7% were overweight, and 8.3% were obese. 73.3% were nulliparas.78.3% had primary infertility, and 21.1% had secondary infertility. The prevalence of male infertility was 6.7%, and female infertility was 81.7%. 81.1% had regular menstrual cycles. 8.3% of patients had medical disorders, and 48% of patients had previous surgeries like polypectomy, polycystic ovarian drilling, and laparoscopy for endometriosis. 71.7% were given the GnRH antagonist stimulation protocol for 8–12 days, and 11–15 eggs were obtained in 66.7% of the patients. 91.7% of frozen embryos were transferred. Conclusion: The success of an ICSI pregnancy is determined by the younger age of the female partner, female factor infertility, antagonist stimulation protocol, and the transfer of a frozen embryo.